Judo as a supportive tool for business and entrepreneurship - Jennifer Berendina Frederique Wichers; Ben Hattink (Nicolaus Copernicus University in Toruń, 2018)
Sports and business or entrepreneurship have frequently been linked to one other in various ways. The world of sport makes use of general management theories and general business and entrepreneurship knowledge for professionalizing the management of sport. Within this article the other way around is explored. The sport in this article is limited to the sport judo. The objective is to find out in what way judo sport can be helpful in developing business and entrepreneurship. The level of using sport/judo as a metaphor in the literature on business and entrepreneurship can be transcended. A comparative study using a multi-method approach was conducted with two groups. One containing entrepreneurs with a background in elite-level judo (including a world champion, an Olympic medal winner, a European champion and a national champion) and another group of entrepreneurs without any background in judo. It can be concluded that there are opportunities that the (basic) principles of judo could be deployed to inspire and support an entrepreneurial orientation. Judo involves both technical and moral principles. The technical principles of judo, in particular, can be translated to the elements of an entrepreneurial orientation. In addition, the moral principles of judo can assist in focusing attention on (corporate) social responsibility and social entrepreneurship.